2020
DOI: 10.1126/science.aba6637
|View full text |Cite
|
Sign up to set email alerts
|

An adhesion code ensures robust pattern formation during tissue morphogenesis

Abstract: Animal development entails the organization of specific cell types in space and time, and spatial patterns must form in a robust manner. In the zebrafish spinal cord, neural progenitors form stereotypic patterns despite noisy morphogen signaling and large-scale cellular rearrangements during morphogenesis and growth. By directly measuring adhesion forces and preferences for three types of endogenous neural progenitors, we provide evidence for the differential adhesion model in which differences in intercellula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 77 publications
3
76
1
Order By: Relevance
“…We imaged transverse sections of the developing neural tube in olig2:egfp ; nkx2.2a:nls-mcherry embryos and larvae from 24 to 72 hpf, a time window that encompasses the specification and migration of MEP glia. We observed that the olig2 pMN domain and the nkx2.2a lateral floor plate of the neural tube, which are distinct at 24 hpf, lose their defined separation at approximately 30 hpf and merge to give rise to one mixed domain by 48 hpf, a phenomenon that has previously been observed and described during OPC specification (Figure 1 - figure supplement 2A) (Kessaris, Pringle, & Richardson, 2001; Kucenas, Snell, et al, 2008; Scott, O’Rourke, Gillen, & Appel, 2020; Soula et al, 2001; Tsai et al, 2020; Xiong et al, 2013). Because MEP glia appear to express both olig2 and nkx2.2a , we hypothesized that similar to OPCs, MEP glia originate from a mixed domain.…”
Section: Resultssupporting
confidence: 79%
“…We imaged transverse sections of the developing neural tube in olig2:egfp ; nkx2.2a:nls-mcherry embryos and larvae from 24 to 72 hpf, a time window that encompasses the specification and migration of MEP glia. We observed that the olig2 pMN domain and the nkx2.2a lateral floor plate of the neural tube, which are distinct at 24 hpf, lose their defined separation at approximately 30 hpf and merge to give rise to one mixed domain by 48 hpf, a phenomenon that has previously been observed and described during OPC specification (Figure 1 - figure supplement 2A) (Kessaris, Pringle, & Richardson, 2001; Kucenas, Snell, et al, 2008; Scott, O’Rourke, Gillen, & Appel, 2020; Soula et al, 2001; Tsai et al, 2020; Xiong et al, 2013). Because MEP glia appear to express both olig2 and nkx2.2a , we hypothesized that similar to OPCs, MEP glia originate from a mixed domain.…”
Section: Resultssupporting
confidence: 79%
“…Mechanisms involving cell-cell interactions to correct initial imprecisions in the spatial organisation of tissues have received considerable attention (Xu et al, 1999;Standley et al, 2001;Rudolf et al, 2015;Dahmann et al, 2011;Addison et al, 2018). Differential cell adhesion between neural progenitors with different cellular identities has been proposed to refine initially disordered patterns (Lei et al, 2004;Xiong et al, 2013;Tsai et al, 2020). However, neither differential adhesion nor cell sorting appear to be the sole explanation for the precision of patterning in the neural tube.…”
Section: Grn Dynamics Contribute To Precise Boundaries Without Attenumentioning
confidence: 99%
“…In the process of blastocyst rhythmic vibration, EPI cells with strong adhesiveness are more likely to gather together, and PrE cells with weak adhesiveness are more likely to fill the gaps between EPI cells. This different adhesion-dependent cell regionalization is also observed during the development of zebrafish embryos 46 .…”
Section: Discussionmentioning
confidence: 53%
“…For example, the fate of the zebrafish mesoderm is regulated by morphogens 47 . In the development of the spinal cord of zebrafish, morphogens work together with cells with different adhesion to enable cells to construct the body accurately and consistently 46 . In early mouse embryos, there is no morphogen gradient has been reported for cell sorting.…”
Section: Discussionmentioning
confidence: 99%